MADING OF POWDERS WITH THE INCREASED FLUIDITY BY NEBULIZED OF METAL FUSIONS BY WATER OF HIGH-PRESSURE IN THE CONDITIONS OF DOUBLE AIR-HYDRONIC TORNADO: Report 2. Model of atomization - Ternovoy, Yurii; Baglyuk, Gennadii; Panova, Vera (Scientific Journal "Metallurgy", 2021)
Water atomization of metal melts in a «spout» is a promising method for producing powdersof any chemical composition with a spheroid particle shape. This shape is not typical fortraditional water atomization. A model explaining and predicting the formation of spheroid powderparticles with a size of more than 10 μm during water atomization is absent in the literature.The work based on the well-known model for water atomization of high-temperature melts.Based on this model, as well as taking into account the experimental and literature data, amodel of melt atomization by high pressure water in an air-water «spout» has been developed.It is shown that the feature of atomization in «spout» is the fragmentation of metal jet by a rotatinggas layer between the melt jet and the water flow, which causes thermophysical conditionsleading to the formation of spheroid particles. The characteristics of the gas layer are determinedby the technical parameters of the water flow, such as pressure, velocity, impact angle,swirl angle, and affect both the shape of the atomized particles and their size. It is shown thatthe thickness of the gas layer is of decisive importance. Stable atomization mode with the formationof spheroid particles is ensured by a minimum distance between the melt jet and the rotatingwater stream, at which the boundary layer of the gas flow has a rate of about 90…100%of the water flow rate. The reasons for the transformation of the shape of the atomized particlesat the transition from atomization by an annular nozzle to a «spout» are considered. The mainreason is the absence of direct contact between the melt jet and liquid metal droplets with water.With optimal atomization parameters, an increase in the solidification time of the droplets,sufficient for their spheroidization, is achieved. Taking into account the proposed model andtechnical parameters of atomization, a formula was obtained to predict the median diameter ofpowder particles.